Analysis of Drainage System for Overcoming Floods on Untung Jawa Island, South Thousand Islands District, DKI Jakarta - Yuda Dwi Yulian (NAROTAMA UNIVERSITY, Indonesia, 2022)
In general, drainage can be used to reduce excess water, whether from rainwater, seepage, or excess irrigation water from an area, so that the function of the area is not disturbed. This study aims to analyze and examine the drainage problems that exist on Untung Jawa Island, South Seribu Islands District, DKI Jakarta, the drainage channels are poorly maintained and frequent flooding. The data used in this study are primary and secondary data, in planning the calculation of flood discharge a 2-year return period is used. For the calculation of flood discharge, the plan uses a rational method and is added to household flood discharge, and the results will be compared with the existing condition of the drainage channel on Untung Jawa Island, South Thousand Islands District, DKI Jakarta. The results obtained that the largest design flood discharge is 3.277 m3/second on channel A8 and the smallest design flood discharge is 0.094 m3/second on channel C5. for the existing condition of the drainage channel, there are 11 channels that fall into the unsafe category because the condition of the existing channel capacity is less than the planned flood discharge, namely channels A2, A3, A4, A5, A6, A7, A8, A10, B2, B3 and B4. Infiltration wells are planned to accommodate the excess flood discharge, and it takes 19 infiltration wells on channel B4, 13 pieces on channel B3, 9 pieces on channel A8, 6 pieces on channel A2, A3, A6 and B2, 4 pieces on channel A7 , 2 pieces on channel A10, 1 piece on channel A4 and A5.